2015
DOI: 10.1371/journal.pone.0140461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Long-Term Trends of Hypertension in Austria: The Impact of Obesity and Socio-Demography

Abstract: BackgroundGlobally there are only less long-term-studies on hypertension available to provide reliable estimates and identify risk groups. This study aims to analyse the prevalence and long-term-trend of hypertension in Austria, recognize affected subpopulations and investigate social inequalities.MethodsThis representative population-based study is based on self-reported data of adults (mean age: 47.7 ± 17.5; n = 178,818) that were taken from five health surveys between 1973 and 2007. An adjustment of self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…In general, hypertension risk is inversely associated with education [15], mostly among women and less consistently among men [911, 39]. In the Brazilian PNS data, however, the picture seemed to be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In general, hypertension risk is inversely associated with education [15], mostly among women and less consistently among men [911, 39]. In the Brazilian PNS data, however, the picture seemed to be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In Western Europe, systolic BP decreased by 2.0 mmHg per decade in men and by 3.5 mmHg or more in women [ 21 ]. The increasing prevalence of obesity and sedentary lifestyle are usually indicated as factors contributing to the adverse trend in arterial hypertension [ 22 , 23 ]. Our data confirmed the increase in the mean BMI of Lithuanian men.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a low SES is associated with worse health, an enhanced prevalence of diseases (Bauer et al, 2009; Burkert, Rásky & Freidl, 2012; Burkert et al, 2012, 2013a, 2013b; Freidl et al, 2001; Holstein et al, 2009; Mackenbach, 2006; Marmot, 2007; Marmot & Wilkinson, 2005; Menke, Streich & Rössler, 2003; Österreichisches Bundesinstitut für Gesundheitswesen (ÖBIG), 2003), and a life expectancy lower by 7 years (The Marmot Review, 2010). Additionally, overweight and obesity are also related to an increased health risk to suffer from diseases (Burkert et al, 2012, 2013a, 2013b; Großschädl et al, 2015; Kiefer et al, 2006; Österreichisches Bundesinstitut für Gesundheitswesen (ÖBIG), 2003) and more mental health problems (Stranges et al, 2014). The results of this study have shown that a low SES as well as a body weight in the obese category is associated with worse self-perceived health, a higher number of chronic conditions as well as more impairment due to ill health.…”
Section: Discussionmentioning
confidence: 99%
“…Lower ratings of health as well as poor health-related behavior in general seem to be associated with obesity (Burkert, Rásky & Freidl, 2012). With rising body mass index (BMI) the risk of ill health increases: Overweight and obesity are associated with an increased health risk to suffer from diseases like diabetes, hypertension, coronary heart disease, osteoarthritis, or hormone-dependent sorts of cancer (Österreichisches Bundesinstitut für Gesundheitswesen (ÖBIG), 2003; Kiefer et al, 2006; Großschädl et al, 2015). Additionally, obesity is associated with less healthy lifestyle, psychological problems and a lower quality of life (Branca, Nikogosian & Lobstein, 2007; Brennan et al, 2009; Kiefer et al, 2006; Kinge & Morris, 2010).…”
Section: Introductionmentioning
confidence: 99%